Răspuns:
Explicație pas cu pas:
a) 7(2x - 1) - 3(4x - 1) = 5(3x + 2) - 1
14x - 7 - 12x + 3 = 15x + 10 - 1
2x - 4 = 15x + 9
15x - 2x = -4 - 9
13x = -13
x = -13 : 13
x = -1
b) 11(x + 2) - 2(2 - 5x) = 8(3 + 4x) + 5
11x + 22 - 4 + 10x = 24 + 32x + 5
21x + 18 = 29 + 32x
32x - 21x = 18 - 29
11x = -11
x = -11 : 11
x = -1
c) 3[2(x + 4) - 3(x - 5)} = 4[3(x + 2) - 4(x + 1)] + 15
3(2x + 8 - 3x + 15) = 4(3x + 6 - 4x - 4) + 15
3(23 - x) = 4(2 - x) + 15
69 - 3x = 8 - 4x + 15
69 - 3x = 23 - 4x
4x - 3x = 23 - 69
x = -46